2020
DOI: 10.3390/genes11050509
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Important Candidate Genes Related to Nutrient Reservoir, Carbohydrate Metabolism, and Defence Proteins during Grain Development of Hexaploid Bread Wheat and Its Diploid Progenitors

Abstract: Wheat grain development after anthesis is an important biological process, in which major components of seeds are synthesised, and these components are further required for germination and seed vigour. We have made a comparative RNA-Seq analysis between hexaploid wheat and its individual diploid progenitors to know the major differentially expressed genes (DEGs) involved during grain development. Two libraries from each species were generated with an average of 55.63, 55.23, 68.13, and 103.81 million reads, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Progress in biotechnological tools, such as the GeneChip ® Wheat Genome array and RNA sequencing, have indicated that the transcripts associated with starch biosynthesis and defense proteins in hexaploid bread wheat are expressed 2-3 weeks after anthesis. The transcripts that are most numerous in growing plants, on the other hand, were associated with storage proteins that are expressed during the developmental phase [198][199][200][201]. While transcriptome analysis was done in hexaploid wheat during grain production [202,203], bread wheat and its wild progenitors have yet to be subjected to a thorough transcriptional characterization.…”
Section: Transcriptome Analysis Uncovers Hidden Information About the Benefits Of Wild Relative Potentialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Progress in biotechnological tools, such as the GeneChip ® Wheat Genome array and RNA sequencing, have indicated that the transcripts associated with starch biosynthesis and defense proteins in hexaploid bread wheat are expressed 2-3 weeks after anthesis. The transcripts that are most numerous in growing plants, on the other hand, were associated with storage proteins that are expressed during the developmental phase [198][199][200][201]. While transcriptome analysis was done in hexaploid wheat during grain production [202,203], bread wheat and its wild progenitors have yet to be subjected to a thorough transcriptional characterization.…”
Section: Transcriptome Analysis Uncovers Hidden Information About the Benefits Of Wild Relative Potentialsmentioning
confidence: 99%
“…This will be useful to understand the changes in wheat grain consistency that occurred during the transition from ancient bread wheat to modern bread wheat. Kaushik et al [201] used RNAseq to study the development of bread wheat grains and their diploid progenitor cells to evaluate gene expression patterns and monitor differentially expressed genes. To analyze gene expression profiles and screen differentially expressed genes, they used transcriptomics methods to compare the expression of key genes in hexaploid bread wheat and its three diploid parents during the entire grain production process.…”
Section: Transcriptome Analysis Uncovers Hidden Information About the Benefits Of Wild Relative Potentialsmentioning
confidence: 99%
See 3 more Smart Citations